2020
DOI: 10.1371/journal.pcbi.1007897
|View full text |Cite
|
Sign up to set email alerts
|

Immunization strategies in networks with missing data

Abstract: Network-based intervention strategies can be effective and cost-efficient approaches to curtailing harmful contagions in myriad settings. As studied, these strategies are often impractical to implement, as they typically assume complete knowledge of the network structure, which is unusual in practice. In this paper, we investigate how different immunization strategies perform under realistic conditions-where the strategies are informed by partiallyobserved network data. Our results suggest that global immuniza… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 82 publications
1
13
0
Order By: Relevance
“…Interventions in this context can be any piece of information (for example, a vaccination campaign or information about transmission risks) that can reduce the risks of transmission. For top-down approaches, the objective of the model is to inform the best targeting strategies, which can be optimized to find highly connected individuals 58 , disconnect social groups 59,60 or be robust to data quality 61 . Bottom-up approaches tend to be more descriptive, often modelled as extensions of classic disease models, assuming random contact within populations and letting disease and information spread and interact 33,62 .…”
Section: Modelling Social and Behavioural Factorsmentioning
confidence: 99%
“…Interventions in this context can be any piece of information (for example, a vaccination campaign or information about transmission risks) that can reduce the risks of transmission. For top-down approaches, the objective of the model is to inform the best targeting strategies, which can be optimized to find highly connected individuals 58 , disconnect social groups 59,60 or be robust to data quality 61 . Bottom-up approaches tend to be more descriptive, often modelled as extensions of classic disease models, assuming random contact within populations and letting disease and information spread and interact 33,62 .…”
Section: Modelling Social and Behavioural Factorsmentioning
confidence: 99%
“…Another important feature that AIS tries to model is the combination of innate and acquired immunization [20]. e innate immune system uses several molecular patterns to identify pathogens; it exists from birth and does not adapt during the life of living organisms.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Interestingly, it is revealed that with a relatively small value of n the immunization strategy may approximate the targeted immunization with full network information. Similar partiallyobserved networks have also been studied for problems like targeted immunization 11,12 , attack robustness 8,13 , and influence maximization 14 . These works, however, are from the perspective of blinding a portion of nodes through random or some specific sampling schemes, which is related but not equivalent to the limited knowledge notion studied in 10 .…”
Section: Introductionmentioning
confidence: 99%